1980
DOI: 10.1007/bf00510258
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 5-HT uptake- and MAO-inhibitors on l-5-HTP-induced excitation in rats

Abstract: The behavioural syndrome caused by L-5-HTP in rats was used for the study of effects of selective 5-HT uptake inhibitors and inhibitors of MAO on central 5-HT receptors. A good correlation was found between the relative potencies of drugs in inhibiting the 5-HT uptake in the rat brain and in intensifying L-5-HTP-induced behavioural stimulation. The potentiation of the L-5-HTP syndrome by the MAO inhibitors correlated with the inhibition of the A- but not of the B-form of the brain monoamine oxidase. In rats tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…This effect was, however, smaller in amplitude than that produced by fluoxetine, suggesting that the increase of cerebral 5-HT level induced by fluoxetine and 5-HTP activates a larger number of 5-HT receptors to induce HTR. Similarly, several studies have previously shown that ADs including SSRIs (citalopram, escitalopram, and fluoxetine) and monoamine oxidase inhibitors (tranylcypromine, pargyline) potentiate the 5-HTP-induced behavioral syndrome (Ortmann et al, 1980;Shimomura et al, 1981;Hyttel et al, 1992;Stórustovu et al, 2004;Sánchez and Kreilgaard, 2004). Notably, the 5-HT 7 receptor antagonist SB-269970 did not modify the 5-HTP-induced HTR but prevented both the AS19-and fluoxetine-stimulating effects.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was, however, smaller in amplitude than that produced by fluoxetine, suggesting that the increase of cerebral 5-HT level induced by fluoxetine and 5-HTP activates a larger number of 5-HT receptors to induce HTR. Similarly, several studies have previously shown that ADs including SSRIs (citalopram, escitalopram, and fluoxetine) and monoamine oxidase inhibitors (tranylcypromine, pargyline) potentiate the 5-HTP-induced behavioral syndrome (Ortmann et al, 1980;Shimomura et al, 1981;Hyttel et al, 1992;Stórustovu et al, 2004;Sánchez and Kreilgaard, 2004). Notably, the 5-HT 7 receptor antagonist SB-269970 did not modify the 5-HTP-induced HTR but prevented both the AS19-and fluoxetine-stimulating effects.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral syndrome induced by L-5-HTP in rats has been used in our laboratory to study the interaction of drugs with the central 5-HT system of rats [Ortmann et al, 1980[Ortmann et al, , 1981a. The method employed for the evaluation of the intensity of behavioral stimulation has been described in detail [Ortmann et al, 19801.…”
Section: Methodsmentioning
confidence: 99%
“…Presynaptic 5-HT depletion does not affect the 8-OHDPAT-induced syndrome in either rats or mice (Dourish et al, 1985;Yamada et al, 1988) indicating that the elements of the 5-HT syndrome are mediated via postsynaptic An increase in 5-HT synthesis and hence 5-HT levels (Hess & Doepfner, 1961;Grahame-Smith 1971a;Ortmann et al, 1980) also elicits the syndrome, as do the direct agonists 5-methoxy-N,N-dimethyltryptamine (Grahame-Smith 1971b;Green et al, 1981), 5-methoxytryptamine (Green et al, 1976), (+ )-lysergic acid diethylamide (LSD) (Trulson & Jacobs, 1976a) and quipazine (Green et al, 1976;. Furthermore 5-HT releasers such as fenfluramine and p-chloroamphetamine (Trulson & Jacobs, 1976b;Deakin & Green, 1978) also cause elements of the 5-HT syndrome.…”
Section: Introductionmentioning
confidence: 99%